2002
DOI: 10.1186/1471-2431-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Salivary testosterone levels in preadolescent children

Abstract: Background: Saliva reflects the plasma free fraction of testosterone which is biologically active, and available for uptake by tissues. Testosterone concentration in saliva, though differing slightly from the concentration of unbound testosterone in serum, is in good correlation with the latter, indicating that salivary testosterone provides a reliable method for determination of serum free testosterone. The study aimed to investigate salivary testosterone levels and their changes in preadolescent children and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…6,2010 and menarche. 33 After menarche the rate of this increase declines, and there is a gradual rise during the teens, with adult levels reached between 18 and 20 years of age 34,35 . Despite these fluctuating levels of hormones, their direct impact on the incidence of URTI remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…6,2010 and menarche. 33 After menarche the rate of this increase declines, and there is a gradual rise during the teens, with adult levels reached between 18 and 20 years of age 34,35 . Despite these fluctuating levels of hormones, their direct impact on the incidence of URTI remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…The sT concentrations in pre-pubertal male subjects remain stable from six to nine years of age [36], and in healthy males an increase is observed, starting from nine to ten years of age, depending on pubertal development. As expected, in our young athletes the mean sT concentrations were significantly correlated with both chronological age and pubertal stages, but regardless of the method of class selection, high intra-class variability and evident inter-class overlaps were observed (Figs.…”
Section: Salivary Steroids At Restmentioning
confidence: 93%
“…Somewhat similar to cortisol, testosterone has been shown to increase linearly in response to exercise, reaching its peak concentration once activity has ceased (Wilkerson et al 1980). Although it provides a non-invasive method of assessing the free, biologically active fraction of circulating testosterone (Ohzeki et al 1991), not many studies present salivary testosterone data on children and adolescents (Ostatníková et al 2002). However, Falgairette et al (1991) reported signiWcant associations between salivary testosterone (SalT), and peak and mean anaerobic power in boys aged 5-16 years.…”
Section: Introductionmentioning
confidence: 95%